Mitigating corruption entrenchment and its effect in Nigeria’s educational system: the policy initiative (2020)
The problem of corruption appears to have permeated every aspect of the Nigerian society since the end of Colonial rule. Corruption drove the military to incur into governance in Nigeria with subsequent coup d'etats. Today, nearly every facet of the Nigerian society appear permeated with corruption inclusive of education at all levels. Common occurrences in educational cycles include; examination malpractices, impersonation in examinations, examination frauds, institutional fraud, admission racketeering, sexual harassments specially sex for grades in higher institutions and the adoption of policies that serve as catalysts to corruption in high places giving an impression and perception that Nigeria is replacing meritocracy with mediocrity. The paper presents a clarification of key concepts on corruption and an overview of perceived policies as 'equal educational opportunity' Federal character policy, quota system and their contributions to the perceived decline of educational standards with attendant consequences on national development. The National common entrance examination to Federal Unity Schools was discussed. The BBC reported sex for grades scandal at the University of Lagos in Nigeria and sex for grade scandal in Obafemi Awolowo University, lle-lfe were highlighted. The paper examined educational policies as well as the centralization and regulation of the administration of education. Recommendations include that the FGN should decentralize the corruption fighting agencies to have sections for secondary and higher schools. Again, Federal Unity schools should be regionalized to help in the area of quality assurance standards maintenance. The problem of corruption appears to have permeated every aspect of the Nigerian society since the end of Colonial rule. Corruption drove the military to incur into governance in Nigeria with subsequent coup d'etats. Today, nearly every facet of the Nigerian society appear permeated with corruption inclusive of education at all levels. Common occurrences in educational cycles include; examination malpractices, impersonation in examinations, examination frauds, institutional fraud, admission racketeering, sexual harassments specially sex for grades in higher institutions and the adoption of policies that serve as catalysts to corruption in high places giving an impression and perception that Nigeria is replacing meritocracy with mediocrity. The paper presents a clarification of key concepts on corruption and an overview of perceived policies as 'equal educational opportunity' Federal character policy, quota system and their contributions to the perceived decline of educational standards with attendant consequences on national development. The National common entrance examination to Federal Unity Schools was discussed. The BBC reported sex for grades scandal at the University of Lagos in Nigeria and sex for grade scandal in Obafemi Awolowo University, lle-lfe were highlighted. The paper examined educational policies as well as the centralization and regulation of the administration of education. Recommendations include that the FGN should decentralize the corruption fighting agencies to have sections for secondary and higher schools. Again, Federal Unity schools should be regionalized to help in the area of quality assurance standards maintenance.